2014
DOI: 10.3892/etm.2014.1977
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype stability of human umbilical cord-derived mesenchymal stem cells during in vitro culture

Abstract: The aim of this study was to investigate whether the chromosomes of human umbilical cord-derived mesenchymal stem cells (hUCMSCs) change following in vitro culture for several generations. In the present study, umbilical cords from two healthy infants following cesarean delivery were collected aseptically and hUCMSCs were isolated by digestion with collagenase and trypsin, and then cultured in vitro. hUCMSCs with fibroblastic morphology were presented from the human umbilical cord tissue after 7 days of adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
1
4
1
Order By: Relevance
“…Some previous studies have reported occurrence of aneuploidy or abnormalities with increased passage number of MSCs [Ben-David et al, 2011;Froelich et al, 2013], and this may be due to chromosomal instability of the cells [Tarte et al, 2010]. However, we could not find any chromosomal aberrations in WJ-MSCs up to P12, while Ruan et al [2014] and Stultz et al [2016] found chromosomal abnormalities at P7 and onwards. In addition, a study by Nikitina et al [2018] has found tetrasomy 8 at passage 12 during in vitro culture of gingival mucosa-derived MSC, whereas Lian et al [2016] have suggested no abnormalities up to P21 in long-term culture of WJ-MSCs.…”
Section: Discussioncontrasting
confidence: 80%
“…Some previous studies have reported occurrence of aneuploidy or abnormalities with increased passage number of MSCs [Ben-David et al, 2011;Froelich et al, 2013], and this may be due to chromosomal instability of the cells [Tarte et al, 2010]. However, we could not find any chromosomal aberrations in WJ-MSCs up to P12, while Ruan et al [2014] and Stultz et al [2016] found chromosomal abnormalities at P7 and onwards. In addition, a study by Nikitina et al [2018] has found tetrasomy 8 at passage 12 during in vitro culture of gingival mucosa-derived MSC, whereas Lian et al [2016] have suggested no abnormalities up to P21 in long-term culture of WJ-MSCs.…”
Section: Discussioncontrasting
confidence: 80%
“…Importantly, according to recent data, each individual UC-MSCs sample exhibited different population doubling rates and reached senescence at different passages due to unique genetic and epigenetic profiles, irrespective of isolation protocol [ 50 ]. A sufficient amount of the starting biomaterial (umbilical cord weight is nearly 40 g) and high telomerase activity of UC-MSCs permit obtaining 10 9 cells from one cord while maintaining their normal karyotype for 6 passages [ 60 , 61 ]. Since passage 7, the telomerase activity of UC-MSCs is significantly reduced; but cell karyotype is stable for at least 25 passages [ 22 , 62 ].…”
Section: The Proliferative Potential and The Karyotype Stability Omentioning
confidence: 99%
“…More recently, polyploid aberrant metaphases (loss of chromosomes 2, 3,5,6,7,8,9, and 16 in ∼ 70% of the cells) were found in 4 human dental pulp-derived MSC lines, in association with the presence of ring chromosomes ( table 2 ) [Duailibi et al, 2012]. Finally, data on chorionic villi-, human umbilical cord-and amniotic fluid-derived MSCs showed normal chromosome complements after 6-10 passages [Poloni et al, 2011;Wang et al, 2013;Ruan et al, 2014] or after 150 days of cryopreservation [Angelo et al, 2012].…”
Section: Mesenchymal Stromal Stem Cellsmentioning
confidence: 99%